Investigating the effects of biofortified wheat flour on plasma zinc, selenium, and enterobacteria in pediatric populations - Usama (Nutrimentum et Curae)
Zinc and Selenium deficiency affects 39% of children in Pakistan, according to the recent National Nutritional Survey 2011. Considering the deficiency states of zinc in our population, interventional strategies have been employed, such as fortification of cereals, food products, and zinc preparations in suspension forms. Zinc biofortification is a better option as wheat flour is the most common and easily assessed food in resource-poor settings compared to the other fortification methods. Although zinc has been used to prevent and treat diarrhoea, the relationship of plasma zinc status with potentially pathogenic bacteria has not been studied.